EVALUATION OF POTENTIAL PROSTHETIC SPACE PARAMETERS IN PARTIAL EDENTATION - Elena-Claudia Sin; Raluca Briceag; Aureliana Caraiane; Gheorghe Raftu; Mihaela-Macrina Manolache; Cristina Nucă; Steliana-Gabriela Buștiuc (Romanian Journal of Medical and Dental Education)
Potential prosthetic space refers to the three-dimensional space corresponding to the edentulous gap available for prosthetic restoration. Failure to accurately assess potential prosthetic space may result in the fabrication of aesthetically and structurally compromised prostheses, ultimately leading to patient dissatisfaction. The aim of the study was to evaluate the potential prosthetic space parameters in partial edentulism. Material and methods: We examined 87 patients from Constanța County, between January 1 and August 31, 2024. The included patients had partial edentation on at least one of the dental arches. In each patient, both arches were preliminarily imprinted with alginate in standard trays and the intermaxillary relationships were also determined and recorded. The study models were mounted in the occlusal device and the parameters characterizing the potential prosthetic space were measured. Results: The age group most affected by partial edentulism is between 50-60 years old (39.08%). The present study revealed a higher prevalence of mandibular edentulism compared to maxillary edentulism. Kennedy Class III was identified as the most frequent pattern of partial edentulism across all age groups in both the maxillary and mandibular arches. The height of the prosthetic space was most affected by secondary shrunken due to abrasion or coronal destruction of the teeth bordering the edentulous gap (27.59%). Also, the amplitude of the potential prosthetic space was most frequently reduced by versions or corporal migrations of the teeth bordering the edentulous gap (49.43%), and the width of the potential prosthetic space was most frequently reduced by atrophy of the alveolar ridge (35.63%). Conclusion. Secondary tooth wear and destruction were the primary factors limiting the height of the potential prosthetic space. Tooth tipping and migration were the main causes of reduced amplitude of the potential prosthetic space. Alveolar ridge atrophy was the most significant factor affecting the width of the potential prosthetic space. These findings underscore the importance of accurate assessment of potential prosthetic space to ensure successful treatment outcomes.